Identifying and measuring the impact of cultural events on hotels' performance. Issue 4 (22nd March 2021) - Piga, Claudio; Melis, Giuseppe
Abstract : Purpose: Focusing on two beer festivals held in Nottingham, England, this study aims to evaluate their indirect impact on the performance of city hotels. This study builds on theoretical insights from the revenue management literature to shed empirical light on the potentially beneficial effects of events on the hotels' performance. This study investigates the impact of the differential support offered by the destination management organisation (DMO) over two years. Design/methodology/approach: Using online prices posted in advance of the events on an online travel agent, the authors assess hotel performance for each day of the events relative to the same day of the week in a week with no event. A similar comparison is made to assess the impact across two different years. In both cases, an ordinary least squares methodology was used. Findings: Both events appear not to have had a strong impact on hotel prices and occupancy in 2016, i.e. when the DMO's promotional effort was more proactive. Instead, in 2017, one event registered higher hotel prices and occupancy both relative to the year before and to the "business as usual" week. Practical implications: The study identifies the existence of an indirect positive economic impact of the events on the hospitality sector. Originality/value: The investigation adopts a more naturalistic experimental design to collect the data, which allows the authors to control for both the impact on prices and occupancy at the level of the single hotel. The evidence is therefore micro-founded. Moreover, results shed light on the role played by the DMO.